2012
DOI: 10.1158/2159-8290.cd-11-0324
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Activation-Loop Phosphorylation by JAK Inhibitors Is Binding Mode Dependent

Abstract: JAK inhibitors are being developed for the treatment of rheumatoid arthritis, psoriasis, myeloproliferative neoplasms and leukemias. Most of these drugs target the ATP-binding pocket and stabilize the active conformation of the JAK kinases. This type-I binding mode leads to an increase in JAK activation-loop phosphorylation, despite blockade of kinase function. Here we report that stabilizing the inactive state via type-II inhibition acts in the opposite manner, leading to a loss of activation-loop phosphoryla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 47 publications
11
107
0
Order By: Relevance
“…JAK2 V617F hyperphosphorylation (32). Our characterization of the nucleotide binding and thermal stability of JH2 ATP binding site mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2 V617F hyperphosphorylation (32). Our characterization of the nucleotide binding and thermal stability of JH2 ATP binding site mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, structural studies showed that the isolated JH1 domains of the four Jaks complexed with ATP-competitive inhibitors adopt an active conformation with an exposed loop (42)(43)(44). With regard to intact Jaks, specific ATP competitive inhibitors that block catalytic function also promote activation loop phosphorylation in cells (45). Moreover, some JH2 mutants of Tyk2 and Jak3 have been described that are catalytically dead but constitutively phosphorylated on the activation loop.…”
Section: Discussionmentioning
confidence: 99%
“…79 Conventional (type 1) adenosine triphosphate-competitive JAK inhibitors bind to and stabilize the active conformation of JAKs, whereas type 2 inhibitors bind to and stabilize the inactive conformation, preventing the kinase from cycling to the active conformation. 81 The JAK2 inhibitor persistence is a phenomenon in which JAK-STAT signaling is reactivated despite the presence of a type 1 JAK2 inhibitor via heterodimerization between activated JAK2 and other JAKs, such as JAK1 or TYK2.…”
Section: Other Jak Inhibitors In Development For Mfmentioning
confidence: 99%